2013
DOI: 10.2337/db13-0785
|View full text |Cite
|
Sign up to set email alerts
|

Lower “Awake and Fed Thermogenesis” Predicts Future Weight Gain in Subjects With Abdominal Adiposity

Abstract: Awake and fed thermogenesis (AFT) is the energy expenditure (EE) of the nonactive fed condition above the minimum metabolic requirement during sleep and is composed of the thermic effect of food and the cost of being awake. AFT was estimated from whole-room 24-h EE measures in 509 healthy subjects (368 Native Americans and 141 whites) while subjects consumed a eucaloric diet. Follow-up data were available for 290 Native Americans (median follow-up time: 6.6 years). AFT accounted for ∼10% of 24-h EE and explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…Experimental reductions in sleep duration support the claim that sleeping time could alter metabolic rates or affect the levels of appetite regulatory hormones such as leptin and ghrelin (30) . An association between insufficient sleep and increased energy intake has been demonstrated in some studies (29)(30)(31) . Sleep restriction was associated with an increase in energy consumption with no change in energy expenditure through PA or leptin and ghrelin concentrations (32) .…”
Section: Sleep In Weight Regulationmentioning
confidence: 87%
“…Experimental reductions in sleep duration support the claim that sleeping time could alter metabolic rates or affect the levels of appetite regulatory hormones such as leptin and ghrelin (30) . An association between insufficient sleep and increased energy intake has been demonstrated in some studies (29)(30)(31) . Sleep restriction was associated with an increase in energy consumption with no change in energy expenditure through PA or leptin and ghrelin concentrations (32) .…”
Section: Sleep In Weight Regulationmentioning
confidence: 87%
“…Multivariable regression models were used to calculate the residuals of EE parameters (24-hour EE and RQ, SMR and AFT) after accounting for known covariates, as previously described (11,24,25). The Pearson's correlation coefficient (r) was used to quantify the associations between EE residuals and food intake measures.…”
Section: Discussionmentioning
confidence: 99%
“…The Pearson's correlation coefficient (r) was used to quantify the associations between EE residuals and food intake measures. Based on the previously reported nonlinear relationship between AFT and BMI showing an inflection point at a BMI ϭ 29 kg/m 2 (11), the relationships between residuals of AFT and food intake measures were calculated separately in subjects with a BMI below and above 29 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleeping and resting energy expenditure were measured in women before and after a weight loss of >10 kg and results indicated that black women had lower body composition-adjusted energy requirements than white women during sleep which could predispose them to greater weight regain [20]. The difference in energy expenditure in the fasting, sleeping state, and the nonactive fed sedentary condition was examined after a 6-year period in over 500 young, healthy subjects [21]. Although this study did not include a weight loss intervention to examine weight regain, awake and fed thermogenesis predicted future weight gain in obese individuals, especially those with high waist circumference and hence abdominal obesity.…”
Section: Weight Maintenance Of Weight Loss In Adultsmentioning
confidence: 99%